Analytical modelling of false blocking problem in wireless ad hoc networks - Chong, W.K. (Springer, 2022)
The false blocking problem is induced by the traditional IEEE 802.11 Request-To-Send/Clear-To-Send (RTS/CTS) handshaking in wireless ad hoc networks such as the emerging Device-to-Device (D2D) ad hoc network. An RTS overhearing node is falsely deferred (blocked) when the RTS/CTS handshaking is unsuccessful. The deferred node does not reply to any other incoming packets during its deferral, resulting in the propagation of false blocking. To mitigate the false blocking problem, various false blocking mitigation schemes were proposed. In this paper, an analytical model based on the Markov chain is developed to mathematically analyse and assess the effectiveness of the false blocking mitigation schemes. The analytical model can be applied to the various medium access control (MAC) protocols in the wireless ad hoc networks. Three mitigation schemes i.e. Ready-to-Send Blocking Notification (RSBN), Request-to-Send Validation (RTS-V), and traditional 802.11 schemes are studied. The results from both the analytical evaluation and simulation evaluation are closely matched. This shows the analytical model is able to accurately represent the behaviour and also provide the performance of various schemes in mitigating the false blocking problem. The analytical model is general and flexible enough that it can be adapted to model any existing and future false blocking mitigation schemes. Â© 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.